1984
DOI: 10.1111/j.1399-0004.1984.tb02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Duplication or insertion in 15q11–13 associated with mental retardation ‐short stature and obesity ‐ Prader‐Willi or Cohen syndrome?

Abstract: Difficulties of differential diagnosis between Prader‐Willi Syndrome and Cohen Syndrome are demonstrated in a 12–year‐old girl with obesity and mental retardation. Cytogenetic studies showed an apparently supernumerary band on chromosome 15 in the proximal region q11‐13. Both parents have a normal karyotype. The aberrant chromosome was derived from an apparently normal paternal chromosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The arrowed chromosomes 15 in Figure 3 of Fuhrmann-Rieger's paper (Fuhrmann-Rieger et al 1984) do not have duplication or insertion; they represent rather normal chromosomes 15. It is impossible to judge from only two pairs of chromosomes 15 as to whether there is a deletion in the unarrowed chromosomes 15.…”
Section: Sirsmentioning
confidence: 97%
“…The arrowed chromosomes 15 in Figure 3 of Fuhrmann-Rieger's paper (Fuhrmann-Rieger et al 1984) do not have duplication or insertion; they represent rather normal chromosomes 15. It is impossible to judge from only two pairs of chromosomes 15 as to whether there is a deletion in the unarrowed chromosomes 15.…”
Section: Sirsmentioning
confidence: 97%
“…There have also been de notlo 15q duplications/triplications identified (13)(14)(15) in association with a similar clinical phenotype, as well as features of the Cohen syndrome (16), PWS (17,18) and AS (19). There have also been de notlo 15q duplications/triplications identified (13)(14)(15) in association with a similar clinical phenotype, as well as features of the Cohen syndrome (16), PWS (17,18) and AS (19).…”
mentioning
confidence: 96%
“…Norio and colleagues (1984) found that several of their patients had been incorrectly diagnosed as having a variety of other conditions including Marfan syndrome, Soto syndrome, and hypothyroidism. Problems associated with obesity and overeating have also resulted in the confusion of Cohen syndrome with Prader-Willi syndrome (Fraccaro et al 1983, Fuhrmann-Rieger et al 1984 although the two conditions appear to be genetically dissimilar (Kondo et al 1990b). The most common misdiagnosis reported by Norio and coworkers (1984) was 'mental retardation of an unknown cause' (p 6).…”
mentioning
confidence: 99%